Lei de Stefan-Boltzmann e efeito Casimir para fótons escuros - Prata, Victor Gustavo Cardoso (2023)
This work considers the presence of dark photons, which can be interpreted as dark matter. These dark photons interact through a mixing term with the usual photons described by Maxwell’s electrodynamics. Using the formalism of Thermo Field Dynamics (TFD), the Casimir effect at zero and finite temperatures, as well as the Stefan-Boltzmann law, are calculated. Our results show that there are corrections due to the presence of dark photons to the usual results of quantum electrodynamics.